STUDI EKSPERIMENTAL PENGGUNAAN IJUK SEBAGAI MATERIAL PERKUATAN LERENG - Bontong, Benyamin; Oktaviana, Ida Sri; Dwijaka, Agus (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2017)
The condition or shape of location of construction is often present in a non-flat terrain. Excavation and dumping of soil usually required in this condition that will result on formation of the slope. The slopes can be made steeper with the help of reinforcement such as by using geotextile, steel and other materials. For small or medium scale construction palm fiber sheet can be used as alternative material. Palm fibers are natural organic fibers that have beneficial properties such as resistant to the influence of solar heat and cold weather, resistant to weathering, and not easily rotten and durable soÂ  it can be used as an option for use as a construction material.This study aims to study the potential use of palm fibers as an alternative material for reinforcement material, especially on the slopes. Palm fibers material used in this research are materials that form a natural fiber sheet. The slope model is formed in a test tub with a width of 30 cm and a height of 80 cm. Sand from Pondo River with 50% of relative density is used as slope forming material.The results showed that the reinforced slopes with fiber sheets with 20 cm vertical spacing and 100 cm length of reinforcement on the test model were able to carry a load of 40 kN at 25 mm (1 inch) settlement, and reach 60 kN at 37.5 mm ( 1 Â½ inches) settlement